ANALISIS PERILAKU KONSUMEN DALAM MEMILIH TOKO UNTUK BERBELANJA (STUDI KASUS PADA TOKO INDOMARET SE-KECAMATAN PAITON PROBOLINGGO). - Fatimah Al-Zahra; Rahmat; Moh. Rifa’i (IZZI: Jurnal Ekonomi Islam, 2022)
The decision to shop or choose a store to shop is very important for minimarket business managers to know. It is not as easy as imagined and not all if done well to increase sales profit. The research uses qualitative methods with descriptive research types. The source of research data was obtained from consumers, namely the Paiton District community who shopped actively, data collection techniques with technical interviews were strengthened by observation and documentation techniques. While the technical analysis of the data by collecting data, reducing data, displaying data, and drawing conclusions. The validity of the data by using triangulation. The results of this study that the things that make consumers shop at Indomaret as follows, namely complete goods, quality security, quality and safe products, clean shops, customer cards, air-conditioned shops, neatly arranged goods determination, promotion of goods/prices, available my point shopping, prices are clear, stores are competitive and there are often new products. The other supporting factors that have implications for purchasing decisions made by consumers include cultural factors, social factors, and personal factors.